Concept Art Animasi 2D sebagai Media Informasi Budaya Desa Wologai Nusa Tenggara Timur - Afif, Riky Taufik; Zhafirah, Fathimah Athiyah; Sumarlin, Rully (Institut Seni Indonesia Yogyakarta, 2025)
Preserving the culture of the Wologai Traditional Village, East Nusa Tenggara by using animation as an information medium to introduce Wologai culture in more depth. This research is focused as an information medium that wants to introduce the culture of the Wologai Traditional Village which is rarely highlighted in the media because of the difficulty of travel access and the remoteness of the village. Concept Art is a tool that can be used as an information medium to introduce the Wologai Traditional Village from the cultural illustrative images visualized in it. The research method uses a qualitative descriptive method with observation instruments and direct interviews with local residents. Wologai culture emphasizes respect for ancestors/elders, accompanied by a belief in unity in diversity. With animation as a medium for conveying information related to culture, the target audience/audience will more easily understand and remember it with the involvement of the five senses in capturing audio and visuals. Implementation in cultural preservation can be reflected in daily activities. In introducing a culture, high accuracy is required in presenting the content contained in 2D animation concept art media to introduce the culture of the Wologai people.